1998
DOI: 10.1073/pnas.95.4.1369
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyl transferase inhibitors cause enhanced mitotic sensitivity to taxol and epothilones

Abstract: An important class of cellular proteins, which includes members of the p21ras family, undergoes posttranslational farnesylation, a modification required for their partition to membranes. Specific farnesyl transferase inhibitors (FTIs) have been developed that selectively inhibit the processing of these proteins. FTIs have been shown to be potent inhibitors of tumor cell growth in cell culture and in murine models and at doses that cause little toxicity to the animal. These data suggest that these drugs might b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(97 citation statements)
references
References 12 publications
7
89
1
Order By: Relevance
“…40 As these drugs are generally non-toxic, we went on to test whether they would be effective when given in combination with traditional cytotoxic drugs. We found that farnesyl transferase inhibitors sensitized cells to the mitotic block induced by paclitaxel and, in combination, the two drugs cause synergistic arrest of cell growth and apoptosis , 41,42 in this report we extend these observations. Epothilones or paclitaxel in combination with farnesyl transferase inhibitors display marked synergy in inhibiting the growth of the prostate cell line DU145 (Figure 8).…”
Section: Discussionsupporting
confidence: 80%
“…40 As these drugs are generally non-toxic, we went on to test whether they would be effective when given in combination with traditional cytotoxic drugs. We found that farnesyl transferase inhibitors sensitized cells to the mitotic block induced by paclitaxel and, in combination, the two drugs cause synergistic arrest of cell growth and apoptosis , 41,42 in this report we extend these observations. Epothilones or paclitaxel in combination with farnesyl transferase inhibitors display marked synergy in inhibiting the growth of the prostate cell line DU145 (Figure 8).…”
Section: Discussionsupporting
confidence: 80%
“…FTI increases cell sensitivity to induction of the G 2 /M block by paclitaxel, suggesting that a farnesylated protein may regulate the mitotic checkpoint. 117 6) A macrocyclic lactone protein kinase C (PKC) activator, bryostatin 1, has been shown to enhance paclitaxel-induced apoptosis of leukemia cells. 118 7) An inhibitor of phosphatidylinositol synthesis, inostamycin, reduces the dosage of paclitaxel required for apoptosis induction in lung carcinoma cells.…”
Section: Enhancement Of Paclitaxel-induced Apoptosis By Adjuvant Treamentioning
confidence: 99%
“…Despite the fact that FTIs cause the phenotypic reversion of Ras-mediated transformation in vitro, these effects seem to be reversible and do not require mutant Ras for activity. [58][59][60] Still, the efficacy of FTIs is improved in combination with cytotoxic chemotherapeutic agents, 59,[61][62][63] and some studies suggest FTIs act synergistically in combination with cytotoxic agents in human lung cancer, which is discussed below.…”
Section: Rasmentioning
confidence: 99%